Alih Aksara dan Alih Bahasa Manuskrip Hikayat Raja Handak - Ayuni, Tresa; Nurizzati (Persona: Kajian Bahasa dan Sastra, 2024)
The objectives of this study are to provide a physical description of the Hikayat Raja Handak manuscript, to present the transliteration of the Hikayat Raja Handak manuscript, and to present the translation of the Hikayat Raja Handak manuscript. This research belongs to the field of philological research. The research method used is the philological method, which involves several stages. The data collection stage utilizes the data inventory method, the manuscript description stage employs the descriptive method, the transliteration stage utilizes the script transfer method, and the translation stage employs the language transfer method. The results of this study include: a description of the Hikayat Raja Handak manuscript, which has been described based on the necessary considerations for manuscript identification and description; the presentation of the transliteration in the Hikayat Raja Handak manuscript. The transcription is carried out following the researcher's transcription guidelines without altering the content or word order of the manuscript; (c) the presentation of the translation of the Hikayat Raja Handak manuscript, which is transliterated from Malay into Indonesian. The translation is done to facilitate readers' comprehension of the Malay language, enabling them to understand and comprehend the contents of the manuscript. The Hikayat Raja Handak manuscript narrates a war between Prophet Muhammad and King Handak, the grandson of Prophet Solomon. King Handak was killed in battle by Ali's sword, known as Zulfikar. Ultimately, King Handak's people were conquered by the Islamic army, thanks to Ali's prowess.